Fertility Differential Among Lower Caste in Lamachaur VDC, Kaski - Gautam, Kedar Raj; Paudel, Pramila (Janapriya Journal of Interdisciplinary Studies, 2017)
Fertility measures the rate of which a population adds to itself by births and is normally assessed by relating the number of births to the size of some section of population. It has been observed that the levels and patterns of fertility vary considerably in various sub groups of the same population in terms of educational attainment, occupation, age at marriage, contraception user etc. This study, therefore, attempts to study of fertility differential among lower caste people. This study is based on descriptive cum analytical research design. Every household of Dalit community in ward no 6, 7 and 8 of Lamachaur VDC are included in the study with a sample population of 85eligible women aged 15-49 years from 85 households. Fertility differential among lower caste people shows that most of the respondents were in the age group of 36-49 and then followed by age group 26-35 and 15-25. Higher fertility is concentrated in the age at marriage from 16 to 19 as compare to other groups of age at marriage. Literate respondents have low fertility as compared to illiterate respondents. Working respondents have high fertility as compared to non-working respondents. The users of contraception have high fertility as compared to non-users of contraception.But, there is no significant relationship between fertility and age of women, age at marriage, literacy status, occupation and users of contraception as measured by chi-square test. It is better to make women literate and to marry at the age after 19 to reduce fertility. Janapriya Journal of Interdisciplinary Studies, Vol. III (December 2014), page: 47-53